The Mother Figure in Contemporary Women’s Theater - Sanda Golopentia (Studies in 20th & 21st Century Literature, 2012)
Five French plays written by women playwrights between the years 1976–88 attest to significant changes in the dramatic presentation of the mother figure. The innovations occur at the general thematic level (with plays centered on the mother–daughter initiating encounter at the moment of giving birth/being born, the reversal of the mother–daughter roles later on in life, trial maternity, willful maternal eclipse, etc.) as well as at the level of the characters’ speech, the setting, and so on. While some of the plays (such as Chantal Chawaf’s Chair chaude, Denise Chalem’s A cinquante ans elle découvrait la mer and Loleh Bellon’s De si tendres liens) put into words typical female experiences rarely or never before voiced in front of a theatrical audience, others (such as Madeleine Laïk’s Transat and Denise Bonal’s Passions et prairies) represent mental experiments that daringly reconfigure the meaning, timing and social as well as personal finality of motherhood.
Keywords: mother; women; mother figure; French; plays; theme; character; female experience; motherhood